2019
DOI: 10.1080/0284186x.2019.1599136
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3D conformal radiation therapy and intensity-modulated radiation therapy in patients with endometrial cancer: efficacy, safety and prognostic analysis

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
3
1
Order By: Relevance
“…Our study showed that IMRT resulted in fewer grade > 3 AE, mostly gastro-intestinal, during treatment, which is consistent with findings of similar studies on the effect of IMRT for cervical or endometrial cancer on treatment-related acute AE. [4,5,19] Besides fewer grade > 3 AE, others additionally reported fewer grade > 2 gastro-intestinal AE during and directly after IMRT, but this could not be confirmed in the present study. [5,9] We did observe significantly fewer grade > 2 AE during follow-up, mainly diarrhea and hematological AE, for women who received IMRT compared to 3DCRT, even up to 5 years, which is in line with other reports on the long-term effects of IMRT versus 3DCRT for women with gynecological malignancies.…”
Section: Discussioncontrasting
confidence: 94%
“…Our study showed that IMRT resulted in fewer grade > 3 AE, mostly gastro-intestinal, during treatment, which is consistent with findings of similar studies on the effect of IMRT for cervical or endometrial cancer on treatment-related acute AE. [4,5,19] Besides fewer grade > 3 AE, others additionally reported fewer grade > 2 gastro-intestinal AE during and directly after IMRT, but this could not be confirmed in the present study. [5,9] We did observe significantly fewer grade > 2 AE during follow-up, mainly diarrhea and hematological AE, for women who received IMRT compared to 3DCRT, even up to 5 years, which is in line with other reports on the long-term effects of IMRT versus 3DCRT for women with gynecological malignancies.…”
Section: Discussioncontrasting
confidence: 94%
“…IMRT and 3D-CRT have been demonstrated an improved treatment outcome and lower skin toxicity in other head and neck cancer, they are the primary radiotherapy techniques for cancer patients during recent decades [18]. However, the prevalence of radiation-related complication with induction chemoradiotherapy in the current literature varies widely [19][20][21]. There is still a lack of evidence and controversy comparing IMRT with 3D-CRT for NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Published literature indicates that the toxic reactions of EBRT mainly include pain, fatigue, hearing impairment, dermoreaction, genitourinary reactions (thamuria, urinary incontinence, cystitis), gastrointestinal reactions (nausea, diarrhea, intestinal obstruction, fecal incontinence), neurological complications (motor neuropathy, sensory neuropathy), soft tissue reactions, and pelvic insu ciency fractures [5,[10][11][12]. Research by Professor Ta M-H and colleagues [37] revealed that the most common toxic reactions are gastrointestinal and genitourinary reactions. Professor Stephanie M. de Boer reported that patients undergoing EBRT treatment experience more intestinal symptoms, which affect daily activities [26].Professor Nout RA found through HRQL analysis that patients receiving EBRT treatment are more likely to need to be close to the toilet due to intestinal issues, which severely restrict their daily activities [24].…”
Section: Discussionmentioning
confidence: 99%